Evaluation of Rice Blast Resistance and R Gene Analysis in Japonica Rice Varieties Tested in the Anhui Region - Qingqing Chen; Yiqun Hu; Wenjie Shen; Aifang Zhang (Agronomy)
Rice blast caused by the ascomycete fungus Magnaporthe oryzea is one of the most widespread and destructive rice diseases worldwide. The most economical and effective strategy for controlling rice blast is the rational use and promotion of disease-resistant varieties. To enhance disease resistance, it is essential to analyze the resistance levels of rice varieties and the role of resistance (R) genes. To investigate blast resistance, R gene distribution, and their contributions in japonica rice, 287 varieties were evaluated through artificial inoculation. PCR detection was also performed using specific primers for eleven R genes. The results showed that 24.4% of the varieties exhibited moderate resistance (MR), indicating an overall moderate resistance level. The frequency of R genes varied significantly: Pib was the most prevalent (89.2%), followed by Pi5 (73.5%), Pita (62.4%), Pia (54.4%), Pikh (48.4%), Pik (41.1%), Pi9 (35.5%), Pizt (23.7%), Pit (10.8%), and Pi1 (10.5%). No Pigm was detected. Among these, Pik, Pi9, Pizt, and Pita contributed most significantly to disease resistance, with contributions of 42.4%, 38.2%, 38.2%, and 33.5%, respectively. The number of R genes detected in the tested varieties ranged from 0 to 9, with most varieties containing more than three genes. The highest proportion of resistant varieties was observed in those carrying six genes. The most common R gene combinations in resistant varieties were ‘Pib + Pita + Pi5 + Pikh + Pik + Pi9’ and ‘Pizt + Pib + Pita + Pia + Pi5 + Pik + Pi9’. In conclusion, these findings provide valuable insights into the breeding and utilizing blast-resistant japonica rice varieties in Anhui Province.